Impact of Inclusive Teaching Strategies on Students’ Learning at Primary Level - Naureen, Asma (International Journal of Psychosocial Rehabilitation, 2020)
This research paper was focused at analyzing the impact of inclusive teaching strategies on the learning of students of class II with and without special needs. The study was experimental in nature in which traditional method of imparting instruction was compared with inclusive instructional strategies. Sample was taken from the school named F.G. Junior Model School, G-7/3-1, Islamabad. Sample size consists of 56 students, twenty- eight students were placed in experimental group and same number of students was in the control group. Both the groups were representative of inclusion, in which there were students from religious/linguistic minorities, slow learners, having low vision or articulation, hyper-actives, etc. Pre-test was used before the treatment started to equate the groups. Treatment of planned inclusive instructional techniques was given to experimental group while control group was taught by ordinary traditional method. The duration of it was two forty days. When the treatment period over, an instructor made post-test was conducted to measure the achievement of the students in the subject of English. First four lessons were taken from the text book for class II. To determine the impact of inclusive instructional strategies on students’ learning in inclusive setting and traditional teaching in inclusive setting, the significance of difference between the scores of experimental and control groups at 0.05 level was tested by applying t-test and analysis was made. It was shown by analysis of data that both the groups (experimental and control) in the beginning of the experiment were approximately equal. The results of post-test have shown that inclusive instructional strategies are more effective than that of traditional method of teaching students at primary level as experimental group scored significantly higher than the control group. The result of the study reflects that inclusive instructional strategies were more effective than traditional method of teaching.